Bond strength of corroded high yield steel bars embedded in normal strength concrete - Thomas Tan (2019)
Strength and performance of reinforced-concrete depend on the good bond strength, between high yield steel bars and concrete, and the effects of corrosion on high yield steel bars in a range of 12 mm, 16 mm and 25 mm diameter reinforced the concrete for its bond strength and are debated endlessly on-site. To investigate the effects of corrosion on the bond strength between the high yield steel bars and concrete, 36 specimens of tensile test, 72 specimens of pullout test and 12 specimens of flexural test conducted. Descriptions of specimen data taken an average of three reading for tensile test and pullout test except for flexural test, uncorroded as control specimen and corroded as a final specimen. High yield steel bars ranges from 12 mm, 16 mm and 25 mm diameter 600 mm long used for tensile test, high yield steel bars ranges 12 mm, 16 mm and 25 mm diameter 800 mm long used as reinforcement bars and embedded vertically in a concrete mold 150 mm x 150 mm x 150 mm concrete grade 20 and concrete grade 30 for pullout test and 1500 mm x 150 mm x 200 mm beam concrete grade 20 for the flexural test. Results show, weight of high yield steel bars reduced by 0.13%, 0.07% and 0.02%, area reduced by 0.13%, 0.07% and 0.02% on 8 months and 12 months reduced by 0.13%, 0.04%, and 0.03%, the area reduced by 0.12%, 0.04% and 0.03% for high yield steel bars 12 mm, 16 mm and 25 mm diameter for the tensile test. The weight of high yield steel bars reduced by 0.14%, 0.05%, and 0.02%, area reduced by 0.13%, 0.06%, and 0.02% on 8 months and 12 months for high yield steel bars 12 mm, 16 mm and 25 mm diameter for pullout test concrete grade 20 and concrete 30. Weight of high yield steel bars reduced by 0.08%, 0.05% and 0.01 %, area reduced by 0.08%, 0.04% and 0.01 % for 8 months and 12 months for the high yield steel bars 12 mm, 16 mm and 25 mm diameter for flexural test concrete grade 20. Weight and area of high yield steel bar 12 mm, 16 mm and 25 mm diameter unchanged for the 4 months for pullout test concrete grade 20 and concrete grade 30, and flexural test concrete grade 20. In sum, the researcher discovered the uncleaned corrosion on high yield steel bars surface influences the bond strength on 4 months of corrosion and the cleaned corrosion on the high yield steel bars surface did not influence the bond strength on the 8 months and 12 months of corrosion for pullout test and flexural test conducted.